Morphological Features of Herbst Corpuscles in the Oropharynx of the Ostrich (Struthio camelus) and Emu (Dromaius novaehollandiae). Issue 5 (18th November 2014) - Crole, Martina R.; du Plessis, Lizette; Soley, John T.
ABSTRACT The distribution of Herbst corpuscles in the oropharynx of the ostrich and emu has recently been documented. However, although the morphology of these mechanoreceptors is well known in neognathous birds, little structural information is available on the Herbst corpuscles of ratites. Tissue sections from those regions of the oropharynx known to possess a high concentration of Herbst corpuscles were sampled from ostrich and emu heads collected after slaughter and prepared for light and transmission electron microscopy. Intra‐oral Herbst corpuscles in the ostrich and emu displayed the same basic components (capsule, outer zone, inner core and axon) described in neognathous birds. However, some important differences were observed, notably, the presence of myofibroblasts in the capsule, sensory cilia in cells of the outer layers, a relatively larger, less organized outer zone and narrower inner core, and variations in the shape of the axon. The previously unreported presence of myofibroblasts in the capsule possibly indicates its ability to contract, thus altering the tension of the capsule, which in turn has implications for the conduction of vibrational stimuli. The sensory cilia in the myofibroblasts of the capsule bordering the outer zone, and in the fibroblasts of the outer zone itself, may play a regulatory role in controlling the contraction of the capsule. Such a function has not previously been reported for Herbst corpuscles in any species of bird. Anat Rec, 298:783–796, 2015. © 2014 Wiley Periodicals, Inc.